Family Survival in the Buluh Purindu Tourism Area during the Covid-19 Pandemic - Ulpa, Fadilla; Indrawadi, Junaidi; Dewi, Susi Fitria; Joni, Erian; Isnarmi, Isnarmi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to see how the survival of street vendors in the reed purindu area. This type of research is a qualitative research with a phenomenological approach. This research uses purposive sampling technique. There are two sources of data in this study, namely primary and secondary data. Data collection techniques using in-depth interviews and observation. The data analysis technique uses data reduction, data presentation, and data verification. The results of this study indicate that family traders in the reed purindu tourist area adapt by doing new habits through programs from the government, namely UKM and LKP as a place to produce woven bamboo and sewing, which aims to earn economic income. Merchant families work together in order to maintain income.